A Geological and geophysical investigation of the diamond runs on Ruigtelaagte and vicinity, in the Bakerville area, Lichtenburg district - Stettler, Edgar Heinz (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1979.